Maximizing The Motor Development Of Elementary School Students Through Physical Education Classes - Reno Faldi Guntur Saputra Sinaga; Muhammad Galih Khadafi; Tiara Apulita Br Kaban; Muhammad Farel Ramadan; Angga Ardiansyah; Amir Supriadi (Jurnal Pendidikan Jasmani (JPJ), 2026)
Developmental growth and learning through physical activity will affect the three domains in education which include cognitive domains (aware of motion), psychomotor domains (biological growth, health, physical fitness), and affective domain (pleasure, self-actualization, self-concept). Problems that appear in this digital era, limited motoric abilities of children because early childhood have been exposed to gadgets early. So that the digital motor skills of children are limited due to the influence of gadgets. The purpose of this study was to determine the level of teacher knowledge of basic movement skills of kindergarten children. This research was conducted with quantitative methods with the type of survey research. Survey research is a study that uses a questionnaire as a research instrument. Research carried out in kindergartens in Cut Nyak Dien's Cluster. 32 kindergarten teachers who are in Cut Nyak Dien Group with educational background from undergraduate education, 65% working period is 2 years. There are 15 kindergarten teachers who have high knowledge in basic motion skills knowledge. There are 6 kindergarten teachers who have knowledge in the moderate category of basic motion skills knowledge in gross motor skills. And there are 12 kindergarten teachers who have low knowledge of basic motion skills knowledge in rough motoric kindergarten children.A total of 18% of teachers have knowledge of locomotor motion and 15% of teachers have no knowledge of non-locomotor movements. TK teachers can implement all three basic motion skills in various motor activities through dancing, gymnastics, and forms of games created by the teacher. Assessment of basic motion skills is done by kindergarten teachers and teachers through observation. 75% of kindergarten teachers know the purpose of stimulating children's basic motion skills, namely to improve children's motor development.